Het liturgisch spreken: een musicologische benadering - Speelman, Willem Marie (Jaarboek voor liturgieonderzoek, 1989)
This article reflects the possibility of an investigation of liturgy as music. The analysis of music in the liturgy might be interesting, but such an analysis will be forced to divide each liturgy in two separate moments, a musical moment and an 'unmusical' one. This separation is problematic, because in most cases it is not clear whether a liturgical moment should be considered as music or as non-music. This problem is solved when we give up the separation and start to consider each liturgical moment as a musical one, in other words to consider liturgy as music. In this article I search for a model for the analysis of the most 'unmusical' moments, liturgical speech, as music. When we investigate liturgy as music, it is clear that we have to forget about the linguistic contents in liturgical speech. This may seem unforgivable, but we needn’t worry: there are many analyses that consider each liturgical moment as a purely linguistic one and forget about the musical form of that moment, so why not turn it the other way round? The model for the musical analysis of liturgy (in this particular case liturgical speech) starts with an analysis of the soundstructure of the liturgy. After this we can describe the sounds on different levels in terms of their parameters and the dimensions of sound as a process. Finally the described sounds can be analysed by putting them back into their context.